Trading Together : Reviving Middle East and North Africa Regional Integration in the Post-COVID Era - Arezki, Rabah; Moreno-Dodson, Blanca; Yuting Fan, Rachel; Gansey, Romeo; Nguyen, Ha; Cong Nguyen, Minh; Mottaghi, Lili; Tsakas, Constantin; Wood, Christina (Washington, DC: World Bank, 2020)
The MENA Economic Update is a product of the World Bank's Office of the Chief Economist for the Middle East and North Africa. This presents the short-term, macroeconomic outlook and economic challenges facing countries in the region.